DIETARY FIBER IN MANAGING CONSTIPATION IN MAJOR BURN TRAUMA PATIENTS: A CASE-SERIES REPORT - Gendis Sekarnegari Putri; Wina Sinaga; Yohannessa Wulandari; Aditya Wardhana (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2026)
Burn injuries result in tissue damage due to exposure to thermal sources or extreme cold. Following burn trauma, systemic inflammatory responses can impair gastrointestinal (GI) function, often leading to constipation. While dietary fiber supplementation is commonly recommended to prevent constipation in the general population due to its ability to enhance intestinal motility, there is limited literature regarding its role in managing constipation among patients with major burn injuries. This case series presents two patients admitted with 34% and 35% total body surface area (TBSA) burns, respectively. Both patients experienced delayed defecation during the first week of hospitalization, without experiencing hypovolemic shock, and had not been administered any sedative agents or vasopressors. Their average dietary fiber intake were 11.1 g and 6.5 g, respectively. One male patient, who was diagnosed with diabetes mellitus (DM), continued to experience constipation until the second week, which improved following dietary modification to a DM-specific regimen. Meanwhile, the female patient showed an improvement in bowel movements in the second week, despite her low fiber intake. Keywords: fiber intake, defecation, major burns